Highly Selective and Potent Human β‐Secretase 2 (BACE2) Inhibitors against Type 2 Diabetes: Design, Synthesis, X‐ray Structure and Structure–Activity Relationship Studies. (5th February 2019) - Ghosh, Arun K.; Brindisi, Margherita; Yen, Yu‐Chen; Lendy, Emma K.; Kovela, Satish; Cárdenas, Emilio Leal; Reddy, Bhavanam Sekhara; Rao, Kalapala Venketeswara; Downs, Deborah; Huang, Xiangping; Tang, Jordan; Mesecar, Andrew D.
Abstract: Herein we present the design, synthesis, and biological evaluation of potent and highly selective β‐secretase 2 (memapsin 1, beta‐site amyloid precursor protein cleaving enzyme 2, or BACE 2) inhibitors. BACE2 has been recognized as an exciting new target for type 2 diabetes. The X‐ray structure of BACE1 bound to inhibitor2 a { N 3 ‐[(1 S, 2 R )‐1‐benzyl‐2‐hydroxy‐3‐[[(1 S, 2 S )‐2‐hydroxy‐1‐(isobutylcarbamoyl)propyl]amino]propyl]‐5‐[methyl(methylsulfonyl)amino]‐ N 1 ‐[(1 R )‐1‐phenylpropyl]benzene‐1, 3‐dicarboxamide} containing a hydroxyethylamine isostere was determined. Based on this structure, a computational docking study was performed which led to inhibitor2 a ‐bound BACE2 models. These were used to optimize the potency and selectivity of inhibitors. A systematic structure–activity relationship study led to the identification of determinants of the inhibitors' potency and selectivity toward the BACE2 enzyme. Inhibitors2 d [ N 3 ‐[(1 S, 2 R )‐1‐benzyl‐2‐hydroxy‐3‐[[(1 S, 2 S )‐2‐hydroxy‐1‐(isobutylcarbamoyl)pentyl]amino]propyl]‐ N 1 ‐methyl‐ N 1 ‐[(1 R )‐1‐phenylpropyl]benzene‐1, 3‐dicarboxamide; K i =0.031 nm, selectivity over BACE1: ≈174 000‐fold] and3 l [ N 1 ‐((2 S, 3 R )‐3‐hydroxy‐1‐phenyl‐4‐((3‐(trifluoromethyl)benzyl)amino)butan‐2‐yl)‐ N 3, 5‐dimethyl‐ N 3 ‐(( R )‐1‐phenylethyl)isophthalamide; K i =1.6 nm, selectivity over BACE1: >500‐fold] displayed outstanding potency and selectivity. Inhibitor3 l is nonpeptide in nature and may pave the way to the development of a new class of potent and selective BACE2 inhibitors with clinical potential. Abstract : Design of selective BACE2 inhibitors : Selective BACE2 inhibitors were designed and synthesized as a potential new treatment for type 2 diabetes. By using X‐ray structural studies of BACE1 along with computational docking approaches with BACE2, a series of potent and highly selective BACE2 inhibitors containing the hydroxyethylamine isostere were designed. This led to the identification of structural determinants important for potency and selectivity for BACE2. Inhibitor3 l exhibited excellent BACE2 potency and high selectivity over BACE1.